THE PERFORMATIVE FUNCTION/POWER OF LITERARY DEVICES IN JUDITH: A SPEECH ACT CONTRIBUTION - R.S. Hobyane (Acta Theologica)
The compositional brilliance of the book Judith has, in research on it, been overshadowed by debates on its fictional nature, historical inconsistencies, canonical debate, gender and moral/ethical issues. While Judith scholars have made significant contributions on historical, ethical and gender matters, this article contends that the composition of Judith is a topic still wide open for exploration. The article suggests that the compositional nature of Judith is an intentional literary strategy of the implied author and has a performative functionwith respect to the reader. In composing the story, the implied author uses literary devices to invite the reader’s participation in the story. The article uses a speech act interpretive angle to explore the identified literary devices in Judith and to demonstrate their performative function to the implied reader. Instead of propagating the story’s fictional nature, ethical issues and historical inconsistencies, this study acknowledges the story’s compositional brilliance, particularly its performative nature with respect to the reader. The article thus asserts that Judith was intentionally composed with innate performative purpose towards the reader.